Inside Back Cover: Single‐Molecule Mechanochemical Sensing Using DNA Origami Nanostructures (Angew. Chem. Int. Ed. 31/2014). Issue 31 (1st July 2014) - Koirala, Deepak; Shrestha, Prakash; Emura, Tomoko; Hidaka, Kumi; Mandal, Shankar; Endo, Masayuki; Sugiyama, Hiroshi; Mao, Hanbin
<x xml:space="preserve">Abstract</x> DNA origami nanotiles have been used as novel multiplex mechanochemical sensors. In their Communication on page 8137 ff., M. Endo, H. Sugiyama, H. Mao et al. show that the binding of specific target molecules to the sensor unlocks the interconnected tiles, and the global topology of the DNA nanostructure rearranges. This process is monitored as mechanochemical signals in real time using optical tweezers.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>